2019
DOI: 10.1111/apa.14742
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐centre study found that strict adherence to guidelines led to computed tomography scans being overused in children with minor head injuries

Abstract: Aim Our primary aim was to calculate the head computed tomography (CT) scan rate in children with a minor head injury (MHI) when the Dutch National guidelines were followed in clinical practice. The secondary aim was to determine the incidence of CT abnormalities and the guideline predictors associated with traumatic abnormalities. Methods We performed a multi‐centre, prospective observational cross‐sectional study in the emergency departments of six hospitals in The Netherlands between 1 April 2015 and 31 Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…First, in our recent multicenter study, we evaluated guidelines adherence and CT use in pediatric MTHI among 1002 children in the northwest region of the Netherlands. 5 We observed that guideline adherence was significantly higher among pediatricians (71%) and emergency physicians (73%), whereas neurologist adherence was lowest at 52%. Strict adherence to the guidelines, however, resulted in overuse of CT scans.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…First, in our recent multicenter study, we evaluated guidelines adherence and CT use in pediatric MTHI among 1002 children in the northwest region of the Netherlands. 5 We observed that guideline adherence was significantly higher among pediatricians (71%) and emergency physicians (73%), whereas neurologist adherence was lowest at 52%. Strict adherence to the guidelines, however, resulted in overuse of CT scans.…”
Section: Discussionmentioning
confidence: 69%
“…4 Also, a recent prospective multicenter study among 1002 children in the northwest region of the Netherlands showed a high CT rate of 44%. 5 This high CT use cannot be explained by increase of patient severity or increase rates of clinically important traumatic brain injuries. 4,6,7 Several factors may contribute to CT scan increase.…”
Section: Introductionmentioning
confidence: 99%
“…This was a planned sub-study of a prospective multicentre observational study that enrolled 1006 children younger than 18 years with MTHI who presented to six emergency departments in The Netherlands between 1 April 2015 and 31 December 2016 [ 9 ]. Exclusion criteria were incomplete data to compare guidelines on a case by case comparison.…”
Section: Methodsmentioning
confidence: 99%
“…The Dutch national guidelines define several major and minor clinical criteria, specified by three age categories, namely under the age of two, between 2 and 5 years and 6 years or more (Supplemental Table 1 ) [ 1 , 8 , 9 ]. For children under the age of two, a CT scan was recommended if they had one or more major criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation